1987
DOI: 10.1007/bf01487261
|View full text |Cite
|
Sign up to set email alerts
|

Conversations with autistic children: Contingent relationships between features of adult input and children's response adequacy

Abstract: The relationship between certain features of adult speech and autistic children's response adequacy was examined within the context of unstructured, dyadic conversations. On separate sessions, four verbal, nonecholalic children were observed talking with their mothers and teachers. Analysis of conversational turns showed that as the number of facilitating features contained in adults' eliciting utterances increased, the proportion of adequate replies from the children increased. In this analysis, facilitating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0
3

Year Published

1990
1990
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 21 publications
(18 reference statements)
1
25
0
3
Order By: Relevance
“…However, this seems unlikely, because the number of PVT test items passed by the two groups of children did not differ, and because mean verbal-IQ was 98 for the children with HFASD and this was assumed to be similar to that for TD children. Rather, the cause could be a cognitive deficit according to the assumption by Curcio and Paccia (1987), who argued that Y/N-Qs might impose an external structure for responses, but that Wh-Qs might not impose such a structure, which children with autism have a greater need for than do TD children (Clark and Rutter, 1981). As for actually responding to Y/N-Qs, the present results showed no difference between children with HFASD and TD children in terms of the extended and minimal verbal responses which can be considered to reflect linguistic ability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this seems unlikely, because the number of PVT test items passed by the two groups of children did not differ, and because mean verbal-IQ was 98 for the children with HFASD and this was assumed to be similar to that for TD children. Rather, the cause could be a cognitive deficit according to the assumption by Curcio and Paccia (1987), who argued that Y/N-Qs might impose an external structure for responses, but that Wh-Qs might not impose such a structure, which children with autism have a greater need for than do TD children (Clark and Rutter, 1981). As for actually responding to Y/N-Qs, the present results showed no difference between children with HFASD and TD children in terms of the extended and minimal verbal responses which can be considered to reflect linguistic ability.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a few attempts (Hewitt, 1998;Louksa et al, 2007), we have made little progress in this area since an assumption made by Curcio and Paccia (1987) regarding their study in which participants were not highfunctioning, as mentioned above. They assumed that an increased need for externally imposed structure (Clark and Rutter, 1981) results in greater difficulty with Wh-Qs because the child must generate the requested information himself rather than simply affirming or negating the information provided by the adult.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…There are however major deficits in pragmatic aspects of language use, both in the range of functions that autistic children express (e.g., Ball, 1978;Mermelstein, 1983;Wetherby & Prutting, 1984) and in their ability to communicate in a discourse setting (e.g., Curcio & Paccia, 1987;Paul & Cohen, 1984;Tager-Flusberg, 1982). Questions remain regarding the existence of a basic semantic deficit in autism: Although autistic children show no problems acquiring words that map onto concrete objects (Tager-Flusberg, 1985, it has been hypothesized that abstract or relational meaning is more seriously impared (Hobson, 1989;Menyuk & Quill, 1985).…”
mentioning
confidence: 99%
“…Moreover, communicative interventions should target the extinction of noncontingent responses. Studies of mother-child conversations involving children with developmental and language delay (Yoder, Davies, & Bishop, 1994) and children with autism (Curcio & Paccia, 1987) have found that mothers are quite skilled at scaffolding and redirecting their child's discourse, even when the child is delayed or disabled. Similarly, Siller and Sigman (2002) found that caregivers of children with autism synchronized their behaviors to their children's attention and activities, and that this parental sensitivity is significantly related to later development of communication skills.…”
Section: Discussionmentioning
confidence: 99%